Interactions between plant endomembrane systems and the actin cytoskeleton - Wang, Pengwei; Hussey, Patrick J. (Frontiers in Plant Science, 2015)
Membrane trafficking, organelle movement and morphogenesis in plant cells are mainly controlled by the cytoskeleton. Not all proteins that regulate the actin cytoskeleton and membrane dynamics in animal systems have functional homologues in plants, especially for those proteins that form the bridge between the cytoskeleton and membrane; the membrane-actin adaptors. Their nature and function is only just beginning to be elucidated and this field has been greatly enhanced by the recent identification of the NETWORKED (NET) proteins which act as membrane-actin adaptors. In this review, we will summarize the role of the actin cytoskeleton and its regulatory proteins in their interaction with endomembrane compartments and where they potentially act as platforms for cell signalling and the coordination of other subcellular events.